Response of tomato (Solanum lycopersicum) to foliar application of micronutrients under low cost protected structure in acidic soil of Meghalaya - VERMA, VEERENDRA KUMAR; JHA, ANJANI KUMAR; VERMA, B C; BABU, SUBHASH; PATEL, R K (The Indian Journal of Agricultural Sciences, 2018)
In North eastern states of India, tomato (Solanum lycopersicum L.) is grown as a spring-summer in open field condition, hence availability is scarce, beside this, acid soil of this region are deficient in some of the important nutrients especially calcium and boron which limit the productivity and quality of the produce. However, there is a lot of scop to grow tomato under protected condition from October to February. To overcome this problem, an experiment was conducted to assess the impact of foliar application of micronutrients on the growth, yield and quality of tomato Megha Tomato-3 variety grown in nutrient stress acidic soil under low cost polyhouse during October-February, 2012-13 and 2013-14.The results showed the significant increase in plant height (162.05 cm), branches per plant (12.27), fruit setting (87.23%), fruits per plant (42.22), fruit weight (75.89 g), yield (76.87 t/ha), shelf life (22.0 days), lycopene content (8.87 mg/100 g) and ascorbic acid (58.06 mg/100 g) under the foliar feeding of mixture of Ca, B, Zn and Cu (100 ppm each) + Mo (50 ppm) nutrients over the treatments having either Ca, B, Zn, Mo, Cu alone or multiplex without calcium as well as control.